If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -5) + 2(3x + 2) = 0 Reorder the terms: 5(-5 + 3x) + 2(3x + 2) = 0 (-5 * 5 + 3x * 5) + 2(3x + 2) = 0 (-25 + 15x) + 2(3x + 2) = 0 Reorder the terms: -25 + 15x + 2(2 + 3x) = 0 -25 + 15x + (2 * 2 + 3x * 2) = 0 -25 + 15x + (4 + 6x) = 0 Reorder the terms: -25 + 4 + 15x + 6x = 0 Combine like terms: -25 + 4 = -21 -21 + 15x + 6x = 0 Combine like terms: 15x + 6x = 21x -21 + 21x = 0 Solving -21 + 21x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 21x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 21x = 0 + 21 21x = 0 + 21 Combine like terms: 0 + 21 = 21 21x = 21 Divide each side by '21'. x = 1 Simplifying x = 1
| 51+38=x | | 5z/6-7z/12 | | r(x)=3 | | 3x^2-5x-1=o | | 5-37=108 | | 4c-17=1/3(8-2c) | | 27/3=x | | 1/4(16f-4)= | | 90+90+143+x=360 | | 31-4= | | 90+90+143+x=180 | | 25-5z=15 | | e+4*2=14 | | 1/4(16f-4) | | x-23=k | | -2(7x-8)+5=14x+21 | | 80=4f+12 | | 4z/7-1=-7 | | -11=-5+3c | | 5=m/4-1 | | -4x-5y=-8 | | m=n+16 | | T=4s+3.67 | | 3j^2-26j+16=0 | | 2cos(3x)*cos(x)=-2 | | 3(1)-y=2(1)+y-1 | | x/8-7=9 | | 4xy-x^2+6x=0 | | 3x+2=8x+2 | | 8(t+2)=72 | | 6n^2-30n^2+24=0 | | (-55/6)=x-(x/2) |